Fulminant Myocarditis with SARS-CoV-2 Infection: A Narrative Review from the Case Studies - Ryohei Ono; Togo Iwahana; Kaoruko Aoki; Hirotoshi Kato; Sho Okada; Yoshio Kobayashi (Canadian Journal of Infectious Diseases and Medical Microbiology)
One of the severe complications of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is myocarditis. However, the characteristics of fulminant myocarditis with SARS-CoV-2 infection are still unclear. We systematically reviewed the previously reported cases of fulminant myocarditis associated with SARS-CoV-2 infection from January 2020 to December 2022, identifying 108 cases. Of those, 67 were male and 41 female. The average age was 34.8 years; 30 patients (27.8%) were ≤20 years old, whereas 10 (9.3%) were ≥60. Major comorbidities included hypertension, obesity, diabetes mellitus, asthma, heart disease, gynecologic disease, hyperlipidemia, and connective tissue disorders. Regarding left ventricular ejection fraction (LVEF) at admission, 93% of the patients with fulminant myocarditis were classified as having heart failure with reduced ejection fraction (LVEF ≤ 40%). Most of the cases were administered catecholamines (97.8%), and mechanical circulatory support (MCS) was required in 67 cases (62.0%). The type of MCS was extracorporeal membrane oxygenation (n = 56, 83.6%), percutaneous ventricular assist device (Impella®) (n = 19, 28.4%), intra-aortic balloon pumping (n = 12, 12.9%), or right ventricular assist device (n = 2, 3.0%); combination of these devices occurred in 20 cases (29.9%). The average duration of MCS was 7.7 ± 3.8 days. Of the 76 surviving patients whose cardiac function was available for follow-up, 65 (85.5%) recovered normally. The overall mortality rate was 22.4%, and the recovery rate was 77.6% (alive: 83 patients, dead: 24 patients; outcome not described: 1 patient).